Becoming Self-in-Relation: Coming of Age as a Pathway towards Wellness for Urban Indigenous Youth in Care - Mellor, Andrea

(untitled) - Cloutier, Denise (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
Two workshops were held with urban Indigenous youth who live in foster care on Lekwungen Territory on southern Vancouver Island. The workshops were informed by guidance from community knowledge holders and Elders and explored the meaning of Indigenous coming of age and adolescence with 15 youth through oral, visual, and text-based activities. Following a thematic analysis of the workshop transcripts, five themes emerged: self-continuity; self-awareness; empowerment; being part of something bigger; and support networks. These themes provide evidence that engaging with coming of age teachings and activities are protective to youth wellness and help youth to build strong foundations from which they can learn about their Indigenous ancestry and history in their own time. (Re)connecting to coming of age teachings is part of a broader discourse of (re)writing narratives that celebrate the strength, leadership, and independence of the urban Indigenous youth community. Although the voices shared reflect young community members living in and around southern Vancouver Island, the essence of our key messages are relevant to the broader Indigenous community and those practicing allyship through education, health care, social work, and other areas of influence.